1998
DOI: 10.1073/pnas.95.12.7179
|View full text |Cite
|
Sign up to set email alerts
|

The role of transmembrane domain 2 in cation transport by the Na–K–Cl cotransporter

Abstract: The human and shark Na-K-Cl cotransporters (NKCC), although 74% identical in amino acid sequence, exhibit marked differences in ion transport and bumetanide binding. We have utilized shark-human chimeras of NKCC1 to search for regions that confer the kinetic differences. Two chimeras (hs3.1 and its reverse sh3.1) with a junction point located at the beginning of the third transmembrane domain were examined after stable transfection in HEK-293 cells. Each carried out bumetanide-sensitive 86 Rb inf lux with cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
75
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(84 citation statements)
references
References 21 publications
8
75
0
Order By: Relevance
“…The current study and those of others (16,17) have highlighted residues that determine ion affinities in NKCC2 and are presumed to be part of the translocation pocket, complementing related findings in NKCC1 (2).…”
Section: Residues Responsible For the Difference In Chloride Affinitymentioning
confidence: 65%
See 3 more Smart Citations
“…The current study and those of others (16,17) have highlighted residues that determine ion affinities in NKCC2 and are presumed to be part of the translocation pocket, complementing related findings in NKCC1 (2).…”
Section: Residues Responsible For the Difference In Chloride Affinitymentioning
confidence: 65%
“…In fact the situation was unlikely to have been that simple, because we previously found that two sets of residues in the beginning of TM2, upstream of the B-to-AF residues (corresponding to GV232 and GL237 in the NKCC2B sequence, Fig. 1), mediate affinity differences for Na ϩ and K ϩ between shark and human NKCC1s (2). Considered together, the NKCC1 and NKCC2 findings argue either: (a) that at least some of the observed K m differences are due to long range effects, or (b) that TM2/ICL1 is not one extended helix, but has at least one hairpin enabling more than one set of amino acid residues to interact with the same transported ion or ion pair.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, considerably less is known about the cell biology and post-transcriptional regulation of NKCC2 than the other key renal transport proteins. Interestingly, Isenring et al (35,63) were able to express an NKCC2-NKCC-1 chimera, in which the 5Ј-untranslated region and cDNA encoding the first 104 amino acids of rabbit NKCC2A were replaced with the corresponding region from human NKCC1. In addition, Payne and Forbush (34) reported that when the proximal region of the NKCC2 N terminus (the first 105 AA) was deleted, immunoreactive proteins were detected in transiently transfected cells.…”
Section: Discussionmentioning
confidence: 99%